Notch4 activation aggravates NF-κB-mediated inflammation in HIV-1-associated nephropathy - Rajni Vaid Puri; Sireesha Yerrathota; Trisha Home; Jessica Y. Idowu; V. Praveen Chakravarthi; Christopher J. Ward; Pravin C. Singhal; Gregory B. Vanden Heuvel; Timothy A. Fields; Madhulika Sharma (The Company of Biologists, 2019)
Notch pathway activation plays a central role in the pathogenesis of many glomerular diseases. We have previously shown that Notch4 expression was upregulated in various renal cells in human immunodeficiency virus (HIV)-associated nephropathy (HIVAN) patients and rodent models of HIVAN. In this study, we examined whether the Notch pathway can be distinctly activated by HIV-1 gene products and whether Notch4, in particular, can influence disease progression. Using luciferase reporter assays, we did not observe activation of the NOTCH4 promoter with the HIV protein Nef in podocytes. Further, we observed upregulated expression of a gamma secretase complex protein, presenilin 1, but not Notch4, in podocytes infected with an HIV-1 expression construct. To assess the effects of Notch4 on HIVAN disease progression, we engineered Tg26 mice with global deletion of the Notch4 intracellular domain (Notch4dl), which is required for signaling function. These mice (Notch4d1/Tg26+) showed a significant improvement in renal function and a significant decrease in mortality compared to Tg26 mice. Histological examination of kidneys showed that Notch4d1/Tg26+ mice had overall glomerular, tubulointerstitial injury and a marked decrease in interstitial inflammation. A significant decrease in the proliferating cells was observed in the tubulointerstitial compartments of Notch4d1/Tg26+ mice. Consistent with the diminished inflammation, kidneys from Notch4d1/Tg26+ mice also showed a significant decrease in expression of the inflammatory cytokine transcripts Il-6 and Ccl2, as well as the master inflammatory transcription factor NF-κB (Nfkb1 transcripts and p65 protein). These data identify Notch4 as an important mediator of tubulointerstitial injury and inflammation in HIVAN and a potential therapeutic target.